The Embera Category of Jai: A Territorial-Cognitive Analysis - Lozano-Rivera, Camilo (Journal of Ecohumanism, 2025)
The Embera category of jai constitutes a vital ontological principle that interweaves agency, knowledge, and vitality across human and non-human domains. This paper examines how jai is both a cognitive category and a territorial phenomenon, deeply embedded in Embera cosmology and knowledge transmission. Drawing from cognitive anthropology and territorial studies, we argue that jai persists due to its alignment with cognitive constraints on cultural transmission while simultaneously being vulnerable to territorial dispossession and geotrauma. Through an interdisciplinary framework, this study explores the effects of forced displacement, extractivism, and state-imposed resettlement on the transmission and embodiment of jai. While cognitive models suggest that certain cultural concepts endure, we reveal that territorial loss fractures the conditions in which jai is enacted and learned. The paper also examines adaptive strategies of the Embera to resist epistemic erasure. By analyzing jai at the intersection of cognition, ontology, and territoriality, this study contributes to broader discussions on indigenous epistemologies, cognitive constraints, and the resistance of cultural knowledge under colonial and environmental pressures.